Synthesis of Green Emitting Multi‐substituted Dibenzodioxins and Related Heteroacenes and Computational Investigation of Substituent Effects on Emission Spectra. Issue 33 (1st September 2020) - Ashok Phadte, Apeksha; Chattopadhyay, Anjan; Banerjee, Subhadeep; Singh Sisodiya, Dilawar; Raghava, Tanya
Abstract: Push‐pull dibenzodioxins with electron withdrawing and donating groups were prepared in good yields through a short and simple synthesis. Strong green emission above 500 nm occurs in those derivatives where there is maximum charge transfer to the most electron deficit terephthalonitrile ring, from proximal cyclic amino donor groups. Theoretical calculations support experimental findings through evaluation of excited state properties. In molecules with a nitro group, the excited state localizes electron density exclusively onto it and twisted nitro geometry was also found. In effect, electronic charge cannot relocate into the molecular plane, rendering them non‐fluorescent. Also, studies on the fluorescent derivatives show that best emission would occur when the donor moiety contains a saturated cyclic amino ring and the amines are 2°. Overall, our study establishes structure‐property guidelines and limits on dibenzodioxin functionalization towards preparing fluorescent derivatives of the same. Abstract : Push‐pull dibenzodioxins and related heteroacenes were prepared for comparison of optical spectra. Computational estimation of excited state properties was performed to confirm the observations. Molecules with secondary cyclic amines in close conjugation with an electron poor terephthalonitirle moiety are the best emitting fluorophores, while nitro derivatives are non‐emissive. This study will promote design and preparation of novel small molecule fluorophores with structural simplicity and high emissivity.